2010
DOI: 10.2466/pms.110.3.751-760
|View full text |Cite
|
Sign up to set email alerts
|

Examining Differences between Center of Pressure Sway in One-Legged and Two-Legged Stances for Soccer Players and Typical Adults

Abstract: To examine stance during the measurement of balance ability, this study aimed to clarify the differences and relationships between balance ability in one-legged (dominant or nondominant leg) and two-legged stances in 25 typical male adults and 25 male soccer players. Balance ability was evaluated with four sway factors: sway velocity, anterior-posterior sway, lateral sway, and high-frequency sway factors. The one-legged stance was more unstable than the two-legged stance, the balance abilities related to two-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
(33 reference statements)
1
24
0
Order By: Relevance
“…This means that the internal reference 17) for motion is established by improvement of perceptual ability, and requires execution of a certain motion before it becomes able to correct detailed motion by comparative matching of the internal reference with actual motion and improving motor skill ability. It was reported that center-of-gravity sway while standing on one leg increased significantly compared to the sway experienced while standing on two legs; centripetal information from the visual, somatosensory, and vestibular labyrinth pathways plays a crucial role in posture control while standing on one leg 18) . Moreover, we have reported that motor-related areas such as the premotor and supplementary motor areas are involved in comparitive matching of somatosensory information and the production of motor program activation during plantar hardness discrimination training like that carried out in the present study 19) .…”
Section: Discussionmentioning
confidence: 99%
“…This means that the internal reference 17) for motion is established by improvement of perceptual ability, and requires execution of a certain motion before it becomes able to correct detailed motion by comparative matching of the internal reference with actual motion and improving motor skill ability. It was reported that center-of-gravity sway while standing on one leg increased significantly compared to the sway experienced while standing on two legs; centripetal information from the visual, somatosensory, and vestibular labyrinth pathways plays a crucial role in posture control while standing on one leg 18) . Moreover, we have reported that motor-related areas such as the premotor and supplementary motor areas are involved in comparitive matching of somatosensory information and the production of motor program activation during plantar hardness discrimination training like that carried out in the present study 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Matsuda et al [10] reported that a simple one-leg balance test with low difficulty does not show clear laterality. Lower limbs are little used dominantly; mostly, they are used similarly, such as when walking.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, laterality of balance ability has been examined by one-leg standing [11] and center of foot pressure (COP) tests during one-leg standing [10]. These tests evaluate static balance ability.…”
Section: Introductionmentioning
confidence: 99%
“…This would allow to maximize, in each period of the athlete's body development, the coherent creation and optimization of a wide set of fundamental motor abilities [11]. Quantitative analysis of postural sway revealed that soccer players present superior balance abilities compared with basketball players, swimmers and nonathletes for single leg stance [21,22]. The balance control occurs three basic control inputs incorporated with the various sensor units: vestibular, visual and proprioceptive mechanoreceptors.…”
Section: Introductionmentioning
confidence: 99%